2001
DOI: 10.1021/ie000660c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Treatment of C−N−O−H Wastes:  Model-Based Reactor Effluent Control

Abstract: In this work, we present model-based control and estimation algorithms developed to control the effluent composition for a hydrothermal oxidation reactor. The reactor is used to oxidize the organic compounds present in the hydrolysate solutions obtained from the destruction of HMXbased high explosives by base hydrolysis. The objective of the model-based control is to minimize the total amount of aqueous nitrogen compounds in the effluent of the reactor while maintaining the desired excess oxygen concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Increasing complexity, models that include simple flow patterns (plug flow or perfect mixing) can give more information about the behavior of particular reactors (e.g. [19,27,[106][107][108]). Models like those need a kinetic model for the reaction and also good predictions of densities.…”
Section: Modeling Of Scwomentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing complexity, models that include simple flow patterns (plug flow or perfect mixing) can give more information about the behavior of particular reactors (e.g. [19,27,[106][107][108]). Models like those need a kinetic model for the reaction and also good predictions of densities.…”
Section: Modeling Of Scwomentioning
confidence: 99%
“…Models like those need a kinetic model for the reaction and also good predictions of densities. Due their simplicity they can easily solve non-stationary reactors and can be used in control systems that demands fast responses [108,109]. To overcome the problems of corrosion and salt deposition, and to improve the energy recovery efficiency, several reactors with complex designs have been developed.…”
Section: Modeling Of Scwomentioning
confidence: 99%
“…The concept of multi-injection has been limited to multistage injection of oxygen , in previous studies. Muske et al reported on the model-based control of an oxygen feed and estimation scheme using a reduced kinetic model.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing complexity, models that include simple flow patterns (plug flow or perfect mixing) can give more information about the behavior of particular reactors (e.g. [19,27,[100][101][102]). Models like those need a kinetic model for the reaction and also good predictions of densities.…”
Section: Modeling Of Scwomentioning
confidence: 99%
“…Models like those need a kinetic model for the reaction and also good predictions of densities. Due their simplicity they can easily solve non-stationary reactors and can be used in control systems that demands fast responses [102,103]. To overcome the problems of corrosion and salt deposition, and to improve the energy recovery efficiency, several reactors with complex designs have been developed.…”
Section: Modeling Of Scwomentioning
confidence: 99%